2015
DOI: 10.1007/s12149-015-1050-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of integrated whole-body PET/MR and PET/CT: Is PET/MR alternative to PET/CT in routine clinical oncology?

Abstract: Integrated PET/MR is a feasible whole-body imaging modality and may score better than PET/CT for the detection of brain metastases. To further prove diagnostic utility, this technique requires further clinical validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Presently, frequent reports have shown that PET/MRI is useful for diagnosing and staging cancers. Even though PET/CT imaging yields better pulmonary nodule detection [23], PET/MRI performs as well as PET/CT in the diagnosis of head and neck tumors [24], prostate cancer [25], and multiple myeloma [26], and PET/MRI is better than PET/CT imaging in the diagnosis of breast cancer [27], colorectal cancer [28], liver cancer [29], abdominal occasional tumors [30], gynecologic tumors [31], lymphoma [32], and bone [33] and brain metastases [34]. Despite that high-speed MR techniques could overcome some of the limitations of MR in detecting gastric cancer, such as motion artifacts, MR has not yet been widely accepted as a standard imaging method for gastric cancer staging.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, frequent reports have shown that PET/MRI is useful for diagnosing and staging cancers. Even though PET/CT imaging yields better pulmonary nodule detection [23], PET/MRI performs as well as PET/CT in the diagnosis of head and neck tumors [24], prostate cancer [25], and multiple myeloma [26], and PET/MRI is better than PET/CT imaging in the diagnosis of breast cancer [27], colorectal cancer [28], liver cancer [29], abdominal occasional tumors [30], gynecologic tumors [31], lymphoma [32], and bone [33] and brain metastases [34]. Despite that high-speed MR techniques could overcome some of the limitations of MR in detecting gastric cancer, such as motion artifacts, MR has not yet been widely accepted as a standard imaging method for gastric cancer staging.…”
Section: Discussionmentioning
confidence: 99%
“…For oncologic imaging, several comparative studies between PET/MRI and PET/CT have been performed within the last couple of years, the majority in smaller-sized patient populations. Depending on the type of cancer investigated, the clinical setting, and the choice of PET radiotracer, these studies have either reported that PET/CT and PET/MRI perform equally well [213], or that PET/MRI has minor to moderate advantages [1421]. It is questionable whether the latter results justify the use of PET/MRI in a routine setting, because the costs for purchase, installation, and maintenance of a PET/MRI system exceed those of PET/CT, and because the scan duration is typically longer with PET/MRI, which leads to a lower patient throughput [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the vast majority of these studies, PET/MRI is performed as an add-on imaging session after the clinical and/or standard of care PET/CT is performed (2931). Ishii et al from Japan compared the diagnostic performance of PET/CT and PET/MRI in 123 patients with a variety of confirmed primary cancers (32). As typical in these types of studies, PET/CT (Biograph mCT, Siemens Healthcare, Erlangen, Germany) was performed first which was then followed by PET/MRI (Biograph mMR, Siemens Healthcare, Erlangen, Germany).…”
Section: Oncologymentioning
confidence: 99%